2022
DOI: 10.1136/neurintsurg-2021-018353
|View full text |Cite
|
Sign up to set email alerts
|

Predicting flow diverter sizing using the AneuGuideTMsoftware: a validation study

Abstract: BackgroundStent sizing remains a challenging task for flow diverter implantation because of stent foreshortening. In this study, we aimed to quantify the change in length after implantation and assess the error in length prediction using AneuGuideTM software.MethodsIn a retrospective cohort of 101 patients with 102 aneurysms undergoing treatment with a pipeline embolization device (PED; Covidien, Irvine, California, USA), we used AneuGuideTM software to obtain measured lengths (ML) and calculated lengths (CL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition, as previously reported, a longer PED may also increase the risk of arterial side branch and perforator occlusion. 13 , 15 , 17 , 20 From this aspect, virtual stent software 16 , 17 should be encouraged given that they may provide distinct advantages in PED length selection and deployment. According to the results of this study, it is recommended that the DL could be as small as possible yet at least greater than 0 mm (this means that the length of the stent is usually larger than the neck of the aneurysm and covers the proximal and distal ends of the aneurysm by at least 5 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as previously reported, a longer PED may also increase the risk of arterial side branch and perforator occlusion. 13 , 15 , 17 , 20 From this aspect, virtual stent software 16 , 17 should be encouraged given that they may provide distinct advantages in PED length selection and deployment. According to the results of this study, it is recommended that the DL could be as small as possible yet at least greater than 0 mm (this means that the length of the stent is usually larger than the neck of the aneurysm and covers the proximal and distal ends of the aneurysm by at least 5 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Software with virtual stent release technology – such as Sim&Size (Sim and Cure, France), 14 Ankyras (Galgo Medical SL, Spain), 14 and AneuGuide™ (ArteryFlow Technology, Hangzhou, China) 15 – were developed to assist clinicians in selecting the braided stent size, as a means to improve the intervention process. Interestingly, some studies have found that the application of these software can reduce the stent size.…”
Section: Introductionmentioning
confidence: 99%
“…1 A–D) using the DSA DICOM image series. The vessel model was then reconstructed based on the level set segmentation method [ 29 ], which is a robust approach and has been applied widely in the area of medical image segmentation [ 30 ].Each case had more than 1 million volume elements containing hexahedra (hex) and split-hexahedra (split-hex) elements. The mesh-independence analysis was done for a patient with a diameter stenosis of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent preliminary study on 101 patients, Tong et al used AneuGuide software, which applies a similar algorithm to ANKYRAS to simulate implantation with the pipeline embolization device. They found a mean simulation error of 6.2% with a good correlation between measured and simulated stent length [32]. Stent length measurements were performed on post-treatment 2D images.…”
Section: Introductionmentioning
confidence: 97%